Comparison of perioperative blood loss of three different posterior nonfusion decompression operations for single-segment lumbar disc herniation - Wang, Liren; Guo, Xing; Song, Zhenjie; Tang, Hanwu; Guo, Haiwei; Li, Ying (Frontiers in Neurology, 2025)
ObjectiveThe perioperative blood loss of percutaneous endoscopic interlaminar discectomy (PEID), unilateral biportal endoscopic (UBE) and open fenestration discectomy (OPD) was compared to provide reference for the selection of clinical surgical methods.MethodsThe clinical data of 260 patients with lumbar disc herniation who underwent PEID, UBE or OPD surgery from March 2020 to February 2024 were retrospectively analyzed, including 100 patients who received PEID surgery, 100 patients who received UBE surgery, and 60 patients who received OPD surgery. Total blood loss and hidden blood loss were calculated according to the linear equation of circulating blood volume, and the hidden blood loss was statistically compared among the three groups.ResultsIn terms of perioperative total blood loss and visible blood loss, the OPD group had the highest total blood loss (408.46 ± 116.89 mL) and visible blood loss (127.17 ± 24.22 mL), followed by the UBE group (304.46 ± 87.55 mL and 51.00 ± 11.15 mL respectively). The PEID group was the least (152.87 ± 54.48 mL and 18.75 ± 5.09 mL). Both the overall differences among the three groups and the pairwise differences were statistically significant (p < 0.05). As for hidden blood loss, the results indicated significant differences between the PEID and UBE groups (p < 0.05), as well as between the PEID and OPD groups (p < 0.05). However, no significant difference was observed between the OPD group and the UBE group (p = 0.22). In terms of operation time, UBE group had the longest operation time (129.67 ± 30.56 min), and OPD group had the shortest operation time (78.73 ± 11.80 min), with statistical difference (p < 0.05).ConclusionIn terms of perioperative blood loss, the PEID group was more minimally invasive than the UBE and OPD groups. Compared with OPD group, UBE group was less invasive, but did not significantly reduce the amount of hidden blood loss after surgery. In terms of operation time, UBE group had the longest operation time and OPD group had the shortest operation time. In terms of hospitalization days, OPD group had the longest hospital stay. In terms of total hospitalization cost, UBE group had the highest total hospitalization cost and PEID group had the lowest total hospitalization cost. The clinician should choose the appropriate surgical plan according to the actual situation of the patient to ensure the efficacy and safety of the operation.